DockFlow: Achieving interoperability of protein docking tools across heterogeneous Grid middleware. (1st October 2010) - Azam, Nabeel; Ghanem, Moustafa; Kalaitzopoulos, Dimitrios; Wolf, Antje; Kasam, Vinod; Wang, Yongjian; Hofmann-Apitius, Martin
Enabling the seamless integration between applications executing on heterogeneous Grid middleware poses a number of challenges to both application scientists and middleware developers. We highlight some of these challenges in the context of designing and implementing DockFlow. DockFlow is a virtual screening environment integrating four Grid-based protein docking tools that execute on different Grid middleware technologies at different locations. We propose extensions that can be applied to any Grid-based workflow system to support the run-time interoperability between the available tools. The extensions are generic, and as an example we describe how they have been implemented in the InforSense workflow system. We also present experimental results that evaluate the tradeoffs between performance and usability of the proposed methods.